Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) ĐK: \(x\ge -1\)
Ta có: \(x^2+\sqrt{x+1}=1\)
\(\Leftrightarrow (x^2-1)+\sqrt{x+1}=0\)
\(\Leftrightarrow (x-1)(x+1)+\sqrt{x+1}=0\)
\(\Leftrightarrow \sqrt{x+1}[(x-1)\sqrt{x+1}+1]=0\)
\(\Rightarrow \left[\begin{matrix} \sqrt{x+1}=0(1)\\ (x-1)\sqrt{x+1}+1=0(2)\end{matrix}\right.\)
Với \((1)\Rightarrow x+1=0\Rightarrow x=-1\) (thỏa mãn)
Với \((2)\Rightarrow x\sqrt{x+1}-(\sqrt{x+1}-1)=0\)
\(\Leftrightarrow x\sqrt{x+1}-\frac{x}{\sqrt{x+1}+1}=0\)
\(\Leftrightarrow x\left(\sqrt{x+1}-\frac{1}{\sqrt{x+1}+1}\right)=0\)
\(\Leftrightarrow x.\frac{x+1+\sqrt{x+1}-1}{\sqrt{x+1}+1}=0\)
\(\Leftrightarrow x.\frac{x+\sqrt{x+1}}{\sqrt{x+1}+1}=0\)
\(\Rightarrow \left[\begin{matrix} x=0\\ x+\sqrt{x+1}=0\end{matrix}\right.\)
Với \(x+\sqrt{x+1}=0\Rightarrow x=-\sqrt{x+1}\Rightarrow \left\{\begin{matrix} x\leq 0\\ x^2=x+1\end{matrix}\right.\Rightarrow x=\frac{1-\sqrt{5}}{2}\)
Vậy \(x=\left\{-1; \frac{1-\sqrt{5}}{2}; 0\right\}\)
b) ĐK: \(-3\leq x\leq 6\)
Ta có: \((\sqrt{3+x}+\sqrt{6-x})^2=3+x+6-x+2\sqrt{(3+x)(6-x)}\)
\(=9+2\sqrt{(3+x)(6-x)}\geq 9\)
\(\Rightarrow \sqrt{3+x}+\sqrt{6-x}\geq 3\) do \(\sqrt{3+x}+\sqrt{6-x}\) không âm.
Dấu "=" xảy ra khi \(\sqrt{(3+x)(6-x)}=0\Leftrightarrow x=-3; x=6\)
Vậy \(x=-3\) or $x=6$
2,\(pt\Leftrightarrow12\left(\sqrt{x+1}-2\right)+x^2+x-12=0\)
\(\Leftrightarrow12\cdot\frac{x-3}{\sqrt{x+1}+2}+\left(x-3\right)\left(x+4\right)=0\)
\(\Leftrightarrow\left(x-3\right)\left(\frac{12}{\sqrt{x+1}+2}+x+4\right)=0\)
Vì \(\left(\frac{12}{\sqrt{x+1}+2}+x+4\right)\ge0\left(\forall x>-1\right)\)
\(\Rightarrow x=3\)
bài 2 rút gọn :
a) \(\sqrt{\left(1-\sqrt{2}\right)^2}+\sqrt{\left(\sqrt{2}-3\right)^2}\)
= \(\left|1-\sqrt{2}\right|+\left|\sqrt{2}-3\right|\)
=\(\sqrt{2}-1+3-\sqrt{2}\)
=2
b) \(\sqrt{4-2\sqrt{3}}+\sqrt{7}-\sqrt{48}\)
= \(\sqrt{\left(\sqrt{3}-1\right)^2}+\sqrt{7}-4\sqrt{3}\)
= \(\sqrt{3}-1+\sqrt{7}-4\sqrt{3}\)
= \(\sqrt{7}-3\sqrt{3}+1\)
c)
Giải pt :
1
a. ĐKXĐ : \(x\ge4\)
Ta có :
\(\sqrt{x+3}-\sqrt{x-4}=1\\ \Leftrightarrow\sqrt{x+3}=1+\sqrt{x-4}\\ \Leftrightarrow x+3=x-3+2\sqrt{x-4}\\ \Leftrightarrow6=2\sqrt{x-4}\)
\(\Leftrightarrow3=\sqrt{x-4}\\ \Leftrightarrow x-4=9\)
\(\Leftrightarrow x=13\) (TM ĐKXĐ)
Vậy \(S=\left\{13\right\}\)
b.ĐKXĐ : \(-3\le x\le10\)
Ta có :
\(\sqrt{10-x}+\sqrt{x+3}=5\\ \Leftrightarrow13+2\sqrt{-x^2+7x+30}=25\\ \Leftrightarrow\sqrt{-x^2+7x+30}=6\\ \Leftrightarrow-x^2+7x+30=36\\ \Leftrightarrow-x^2+7x-6=0\\ \Leftrightarrow-x^2+x+6x-6=0\\ \Leftrightarrow-x\left(x-1\right)+6\left(x-1\right)=0\\ \Leftrightarrow\left(x-1\right)\left(6-x\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=1\left(TMĐKXĐ\right)\\x=6\left(TMĐKXĐ\right)\end{matrix}\right.\)
Vậy \(S=\left\{1;6\right\}\)
\(a,\sqrt{x^2+3}=\sqrt{x+3}\)
\(\sqrt{x^2+3}^2=\sqrt{x+3}^2\)
\(\left|x^2+3\right|=\left|x+3\right|\)
\(\orbr{\begin{cases}x^2+3=x+3\\x^2+3=-x-3\end{cases}\orbr{\begin{cases}x^2=x\\x^2=-x-6\end{cases}}}\)
\(\orbr{\begin{cases}x=1\\x^2+x+6=0\end{cases}}\)
\(\orbr{\begin{cases}x=1\\x^2+x+\frac{1}{2}+\frac{11}{2}=0\end{cases}}\)
\(\orbr{\begin{cases}x=1\left(TM\right)\\\left(x+\frac{1}{4}\right)^2+\frac{11}{2}=0\left(ktm\right)\end{cases}}\)
\(b,\sqrt{3x+2}^2=\sqrt{x}^2\)
\(\left|3x+2\right|=\left|x\right|\)
\(\orbr{\begin{cases}3x+2=x\\3x+2=-x\end{cases}\orbr{\begin{cases}2x+2=0\\4x+2=0\end{cases}\orbr{\begin{cases}x=-1\left(TM\right)\\x=-\frac{1}{2}\left(TM\right)\end{cases}}}}\)
\(c,\sqrt{3-x}^2=\sqrt{x-3}^2\)
\(\left|3-x\right|=\left|x-3\right|\)
\(\orbr{\begin{cases}3-x=x-3\\3-x=3-x\end{cases}}\)
\(\orbr{\begin{cases}x=3\left(TM\right)\\3=3-0x\left(KTM\right)\end{cases}}\)